PENAPISAN BAKTERI ENDOFIT PENDEGRADASI PATI DARI TAMAN NASIONAL GUNUNG HALIMUN (TNGH) - Melliawati, Ruth; Sulistiyowati, Eki (LIPI Press, 2012)
In order to produce a good quality biological product such as starch, an enzyme namely amylase was crucially required. Potential microbe could generate sugar through starch degradation. Endophytic bacterias were found on various tissues of plant. Indonesia is really potential to become a source of advantagous endophytic bacteria with its rain forests. The purposes of this research were (1) to screen which endophytic bacteria could degradate starch, (2) to determine the type of reducing sugar generated and (3) to determine the value of amylase activity and theaccumulation of reducing sugar. This research was expected to give some information about the use of endophytic bacteria as an alternative of sugar producer for several industrial sectors. The sceening was practiced to the 30 isolated endophyt bacteria from the plants in Halimun Mountain National Park. Those bacteria was inoculated at a medium named Potato Starch Agar (PSA). The ability to degradate starch could be known when there were clear zones around them. The kinds of sugar were detected by TLC method while the analysis of the amount of reducing sugar and experiment about the activity of amylase were done based on Somogy-Nelson method. The sceening test result that 12 isolates bacteria could grow well on PSA. Three of them generated large clear zones. They wereHL.72 B.153, HL.74 B.156 and HL.89 B.197, with the width of each clear zone were 5,31 cm2, 2,69 cm2 and 6,6 cm2. The experiment of enzymatic activity and the accumulation of of reducing sugar of three choosen isolated bacterias showed that the highest result was HL.89 B.197 with 556,67 Unit and its sugar accumulation value was 631,89 ppm. Then the amylase activitys value of HL.72 B.153 was 505,3 Unit and its sugar accumulation value was 472,29 ppm. The last result was HL.74 B.156 with the amylase activitys value was 263,73 Unit and its sugar accumulation value was 330,21 ppm. The result of TLC showed that a fermentation of HL.72 B.153 was Rf=0,42 of Rf value was same as galactose. HL.74 B.156 Rf value was 0,54 was same as the Rf value of fructose and the Rf value of HL.89 B.197 was 0,54 which was same as the Rf value of glucose.